A Note on an ECM asymmetry in Spanish - Lorena Castillo Ros (Universitat Autònoma de Barcelona, 2017)
This paper discusses an asymmetry in Spanish ECM structures whereby NP passivization improves if the embedded clause is a non-infinitive. The facts are accounted for by assuming that structural Case can only be assigned once within a relevant domain (a phase; cf. Chomsky 2000, 2001). This raises non-trivial questions about Case competition and Case resistance facts, opening new perspectives on the study of the Case/agreement systems and their parametric variation.